Using a Powered Bone Marrow Biopsy System Results in Shorter Procedures, Causes Less Residual Pain to Adult Patients, and Yields Larger Specimens - Berenson, James R; Yellin, Ori; Blumenstein, Brent; Bojanower, Deanna; Croopnick, Jonathan; Aboulafia, David; Upadhyaya, Gargi; Spadaccini, Cathy (Diagnostic pathology, 2011)
Background In recent years, a battery-powered bone marrow biopsy system was developed and cleared by the U.S. Food and Drug Administration to allow health care providers to access the bone marrow space quickly and efficiently. A multicenter randomized clinical trial was designed for adult patients to determine if the powered device had advantages over traditional manually-inserted needles in regard to length of procedure, patient pain, complications, user satisfaction, and pathological analysis of the specimens. Methods Adult patients requiring marrow sampling procedures were randomized for a Manual or Powered device. Visual Analog Scale (VAS) pain scores were captured immediately following the procedure and 1 and 7 days later. Procedure time was measured and core specimens were submitted to pathology for grading. Results Ten sites enrolled 102 patients into the study (Powered, n = 52; Manual, n = 50). Mean VAS scores for overall procedural pain were not significantly different between the arms (3.8 ± 2.8 for Powered, 3.5 ± 2.3 for Manual [p = 0.623]). A day later, more patients who underwent the Powered procedure were pain-free (67%) than those patients in the Manual group (33%; p = 0.003). One week later, there was no difference (83% for Powered patients; 76% for Manual patients.) Mean procedure time was 102.1 ± 86.4 seconds for the Powered group and 203.1 ± 149.5 seconds for the Manual group (p < 0.001). Pathology assessment was similar in specimen quality, but there was a significant difference in the specimen volume between the devices (Powered: 36.8 ± 21.2 mm 3 ; Manual: 20.4 ± 9.0 mm 3 ; p = 0.039). Two non-serious complications were experienced during Powered procedures (4%); but none during Manual procedures (p = 0.495). Conclusions The results of this first trial provide evidence that the Powered device delivers larger-volume bone marrow specimens for pathology evaluation. In addition, bone marrow specimens were secured more rapidly and subjects experienced less intermediate term pain when the Powered device was employed. Further study is needed to determine if clinicians more experienced with the Powered device will be able to use it in a manner that significantly reduces needle insertion pain; and to compare a larger sample of pathology specimens obtained using the Powered device to those obtained using traditional manual biopsy needles.